A política de incentivo à cabotagem (br do mar) prevista no projeto de lei n° 4.199/2020 e a aplicabilidade da lei do pavilhão aos contratos de trabalho dos tripulantes de embarcações estrangeiras afretadas por tempo - Soares, Vitor Hugo Sombra (2021)
Aiming to diversify and balance the Brazilian logistics matrix, which is hostage to the use of its highways for cargo transport, the Federal Government, on August 11, 2020, sent Bill No. 4,199 to the National Congress, which institutes the Policy of Incentive to Cabotage, also known as BR do Mar. Through this, the Federal Government aims to encourage, increase the competitiveness of cabotage in Brazil by removing bureaucratic obstacles, creating new routes and reducing handling costs, thus resulting in a greater balance of the Brazilian logistics matrix. The Project also foresees the possibility of chartering a foreign vessel from its wholly-owned foreign subsidiary to operate cabotage navigation. Among the requirements, there is a need for part of the crew to be Brazilian, however, the Project provides that the employment contracts of crew members operating in a foreign chartered vessel will be subject to application of the international conventions, which results in the application of the flag state law to the Brazilians members of the crew operating in Brazilian cabotage. Therefore, this study aims to analyze the preponderance of the flag state law in opposition of the Brazilian Law to the employment contracts of crew members operating in foreign vessels chartered in the manner of the BR do Mar, analyzing the main advantages and disadvantages, the risk of using flags of convenience, how the Brazilian jurisprudence has positioned itself and, finally, proposing clarifications to the problem under study. Keywords: Flag state Law; BR do Mar; Cabotage Incentive Policy; Maritime Law